Statement of the problem modeling the process vacuum microwave drying for determining temperature fields in foamed suspensions - V. V. Tkach; G. O. Magomedov; A. A. Shevtsov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The aim of the study is to formulate a mathematical model of the process of vacuum microwave drying to determine the temperature fields in foamed suspensions. With the obvious advantages of microwave drying in a vacuum, the possibility of overheating of the dried material is not excluded, which affects its quality. Therefore, the limitation on the temperature of the material during drying must be taken into account in the simulation.Method. The study is based on the methods of simulation computer modeling.Result. The formulation of the modeling problem for determining the temperature fields in foamed suspensions in a wide range of regime parameters is proposed.Conclusion. Increasing the accuracy of simulation results by improving the mathematical description is the basis of modern research in the field of technology and equipment for vacuum microwave drying.